ABSTRACT: MUNINN LIBRARY - A VIRTUAL GAMIFIED LIBRARY (CIPEEX, 2025)
According to the 5th edition of the "Portraits of Reading" survey in Brazil, there was a significant drop of approximately 4.6 million readers between 2015 and 2019. The decline in active readers across Brazil, due to lack of time or interest, presents a common problem: individuals often intend to read but abandon the effort due to difficulties finding viable sources or spending excessive time and money on acquiring books.The Muninn initiative aims to simplify and enhance the reading experience by providing efficient research methods, allowing users to focus on reading rather than searching for content. Beyond book reading, users can review books with others and consolidate their personal collections on the platform.The software development employs the Scrum method, focusing on the MVP of the product, created using user stories and team goals. Functionality prioritization for Week Sprints is determined by Planning Poker. Muninn's visual identity was designed for intuitive use, employing persona analysis. Low-saturation, warm tones reduce eye strain, adhering to color psychology principles. The block structure simplifies comprehension, following Gestalt principles. Partial interface coverage of elements suggests continuation, aligning with UX rules. The digital reader screen supports element hiding for focused reading.The project has resulted in prototype screens for the site: profile, home, and digital reader pages, created using the FIGMA platform, showcasing element arrangements, applied rules, and the platform's initial design.
Keywords: library; gamification; reading